Effect of traditional Chinese exercise on type 2 diabetes An overview of systematic reviews - Huang, Liyuan; Li, Ran; Qin, Jinming; Dong, Tianqi; Cai, Yihui (The Journal of the International Society of Chinese Health Practices, 2021)
See PDF for details